Simultaneous Determination of Fenofibrate, its Metabolite and Co- Formulated/Administered Statins Using Reverse Phase TLC-Densitometry and HPLC-UV Methods: Application in Human Plasma - El-Din Ahmad Salama, Nahla Nour (Current Chromatography, 2015)
Rapid reverse phase TLC-densitometry and HPLC-UV detection methods were developed and validated for simultaneous determination of fenofibrate (FBT), its metabolite fenofibric acid (FFA) and co-formulated/ co-administered statins; rosuvastatin (RST) or atorvastatin (AST). The first method was based on reversed phase (C18) thin layer chromatographic separation of the studied drugs followed by densitometric measurements. The second method was based on isocratic reverse-phase liquid chromatographic separation of the selected compounds on C18 column (250 x 4.6 mm, 10 µ) maintained at controlled temperature (25°C). The mobile phase consisted of acetonitrile-water (82:18, v/v) and quantification was made at 254 nm for both methods. The flow rate was maintained at 1.5 mL/ min. The calibration graphs were linear in the concentration ranges of 0.25 - 4 µg/ spot and 5.0 - 50 µg mL-1 for C18 TLC-densitometry and HPLC-UV methods respectively. The developed methods were validated for specificity, linearity, precision, accuracy, and robustness. All criterions were within the acceptable range for the studied compounds. Statistical analyses proved that the investigated assays were incomparable. Moreover HPLC method was applied for determination of FBT and its metabolite and co-administered statins in human plasma. The assay procedure involved a simple one-step extraction of FBT, FFA, RST and AST from human plasma by salting out with sodium chloride and 0.1% orthophosphoric acid. The chromatographic separation was obtained within 5.4 min.
Keywords: metabolite